PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN Studi Kasus PT Sarinah (Persero) Jakarta - Woro Juni Diastuti (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: The purpose of this research is to investigate the effects of leadership style and job satisfaction on employee performance. Using these variables based on the results ofprevious studies, with the taking of secondary data from the literature and primary data in the form of respondents with proportional stratified random sampling.The research was conducted at PT. Sarinah (Persero) Jakarta, by taking 166 employees as research subjects. Data were analyzed using multiple linear regression analysis techniques. The results show the effect of leadership style on employee performance is significantly positive; the effect of job satisfaction on employee performance is significantly positive and the effects of leadership style and job satisfaction on employee performance simultaneously is significant and positive.Keywords: Leadership Style, Job Satisfaction, Employee Performance